Narration of Islamic Values in the “Sang Piatu” Folklore - Ali, Ahmad Jum'a Khatib Nur; Mohammad Siddiq; Robingah (Mitra Palupi, 2024)
Background: Indonesia is rich with cultural diversity as the identity of the Indonesian nation. One form of diversity is folklore. As a cultural product, folklore contains value narratives that are important for national character building. Purpose: This research focuses on the narrative of Islamic value education content in folklore. The purpose of this research article is to find out the narrative of Islamic value education content conveyed in the Sang Piatu folklore. Design and methods: The research method used is descriptive-qualitative with a narrative structure and value approach as a conceptual reference for analysis. The research data was collected by using documentation technique. The object of analysis is the folklore of Sang Piatu from Bengkulu which was published as a non-educational textbook in 2016. Results: The results showed that the Sang Piatu folktale has a narrative structure: equilibrium, disruption, disequilibrium (recognition, resettlement), and new-equilibrium. The value of Islamic education is about seeking knowledge and sincerity which are narrated implicitly and explicitly through direct dialog or storytelling narrators. The folklore of the Sang Piatu becomes an educational medium to form a personality with Islamic values.